The Influence of Perfectionism and Self-Esteem on Academic Stress in Students during Online Learning - Nur Hasanah, Rosy; Azalia Wenvi Annora, Baiq; Sulistiyorini, Sulistiyorini (Lafadz Jaya Publisher, 2024)
This study aims to determine the effect of perfectionism and self esteem on academic stress in college students during online learning. The Research method used is a quantitative method with multiple regression analysis techniques. The sampling technique in this study is convenience sampling. The sample in this study amounted to 299 students, consisting of 81 males and 281 females. The measuring tools used in this research are Educational Stress Scale for Adolescents (ESSA), Frost Multidimensional Perfectionism Scale (FMPS), dan Rosenberg Self-Esteem Scale (RSES). The result showed that self-esteem didn’t significantly affect academic stress, but when together with perfectionism (maladaptive perfectionism) these two variables interact and contribute significantly to academic stress. The results of the coefficient of determination show that the contribution of perfectionism and self-esteem is 4,4% to academic stress. This shows that 4.4% of academic stress is influenced by perfectionism (maladaptive perfectionism) and self-esteem, 95.6% is influenced by other variables not examined in this study.